Дослідження показників пожежної небезпеки полімерних композитних матеріалів систем фасадного утеплення будинків - Довбиш, В.В.; Новак, С.В.; Пресняк, І.С.; Третьякова, О.В. (Актуальні проблеми транспортної медицини, 2008)
Проведены лабораторные (маломасштабные и стендовые) испытания 17 композитных облицовочных материалов систем утепления фасадов зданий с вентилируемой воздушной прослойкой по показателям горючести, воспламеняемости, дымообразования и токсичности продуктов горения. Показано, что при решении вопроса выбора материалов следует учитывать комплекс предложенных показателей. Однако полученные данные свидетельствуют об ограниченных возможностях традиционных методов лабораторных испытаний при комп лексной оценке систем утепления зданий, что требует совершенствования методической базы испытаний пожарной безопасности материалов. Laboratory researches of 17 composite facing materials in small scale and testing ground are lead. These were warming systems of buildings facades with a ventilated air layer. In made researches parameters of combustibility, ignition, smoke formation and combustive products toxicity are carried out. It is shown, that at the election of materials choice it is necessary to take into account the complex of the suggested parameters. However the traditional methods aren’t abdicate for the complex testified. It was shown, that it is actual to improving a renewed system of laboratory control and methodic base of materials fire safety testing perfection.